2016
DOI: 10.3389/fpsyg.2016.01050
|View full text |Cite
|
Sign up to set email alerts
|

Experimental But Not Sex Differences of a Mental Rotation Training Program on Adolescents

Abstract: Given the importance of visuospatial processing in areas related to the STEM (Science, Technology, Engineering, and Mathematics) disciplines, where there is still a considerable gap in the area of sex differences, the interest in the effects of visuospatial skills training continues to grow. Therefore, we have evaluated the visuospatial improvement of adolescents after performing a computerized mental rotation training program, as well as the relationship of this visuospatial ability with other cognitive, emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 65 publications
5
25
0
4
Order By: Relevance
“…We demonstrated that behavioral improvements in mental rotation ability are likely due to the combination of improved rotation (VSN, motor cortex) and encoding more detailed representations (LOC, saccade amplitude). The current study replicated several previous studies (Leone, Taine & Droulez, 1993;Meneghetti et al, 2017;Provost, Johnson, Karayanidis, Brown & Heathcote, 2013;Rodán et al, 2016;Wright et al, 2008) which found that training on a mental rotation task improves performance on that same task. The question that is less certain from the previous literature is when training on one task can transfer to other tasks or other stimuli (Uttal et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We demonstrated that behavioral improvements in mental rotation ability are likely due to the combination of improved rotation (VSN, motor cortex) and encoding more detailed representations (LOC, saccade amplitude). The current study replicated several previous studies (Leone, Taine & Droulez, 1993;Meneghetti et al, 2017;Provost, Johnson, Karayanidis, Brown & Heathcote, 2013;Rodán et al, 2016;Wright et al, 2008) which found that training on a mental rotation task improves performance on that same task. The question that is less certain from the previous literature is when training on one task can transfer to other tasks or other stimuli (Uttal et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The goal of the current study was to examine the possibility of near transfer (transfer to a new category of stimuli in an analogous spatial reasoning task). Other studies have examined how mental rotation skills transfer to other tasks such as spatial paper folding (Wright et al, 2008), perspective tests (Meneghetti et al, 2016, Meneghetti et al, 2017, or measures of working memory capacity (Rodán et al, 2016) with varying results, leaving conclusions uncertain. Therefore, we used an identical same/different task procedure for the trained (cubes task) and untrained stimulus categories (molecules task) to determine the degree of near transfer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that between 3 and 5 years of age, children still have not been differentially exposed to spatial experiences that could be influencing the observed spatial performance at later stages ( Sander et al, 2010 ). Actually, a recent work on MR training with teenagers found no sex differences before or after training for spatial ability ( Rodán et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%